Ecosystem functioning impacts of the invasive seaweed Sargassum muticum (Fucales, Phaeophyceae). Issue 1 (11th December 2013) - Vaz‐Pinto, Fátima; Olabarria, Celia; Arenas, Francisco; Dunton, K.
<x xml:space="preserve">Abstract</x> Ongoing changes in natural diversity due to anthropogenic activities can alter ecosystem functioning. Particular attention has been given to research on biodiversity loss and how those changes can affect the functioning of ecosystems, and, by extension, human welfare. Few studies, however, have addressed how increased diversity due to establishment of nonindigenous species (NIS) may affect ecosystem function in the recipient communities. Marine algae have a highly important role in sustaining nearshore marine ecosystems and are considered a significant component of marine bioinvasions. Here, we examined the patterns of respiration and light‐use efficiency across macroalgal assemblages with different levels of species richness and evenness. Additionally, we compared our results between native and invaded macroalgal assemblages, using the invasive brown macroalga Sargassum muticum (Yendo) Fensholt as a model species. Results showed that the presence of the invader increased the rates of respiration and production, most likely as a result of the high biomass of the invader. This effect disappeared when S. muticum lost most of its biomass after senescence. Moreover, predictability–diversity relationships of macroalgal assemblages varied between native and invaded assemblages. Hence, the introduction of high‐impact invasive species may trigger major changes in ecosystem functioning. The impact of S. muticum may be related to its greater biomass in the invaded assemblages, although species interactions and seasonality influenced the magnitude of the impact.